COLLECTIVE ARGUMENTATION AND PARTICIPATION IN SOLVING GEOMETRY PROBLEMS IN THE MATHEMATICS CLASSROOM - wulandari, evi novita; Juniati, Dwi; Khabibah, Siti (JME (Journal of Mathematics Education), 2024)
Collective argumentation is a process in learning that can be used to train communication skills, collaboration, and understanding of mathematical concepts. In this process, both teachers and students play an active role, which is called participation. This study aims to describe the structure of collective argumentation and student participation in solving geometry problems in the classroom. This research method is a qualitative case study. The subjects in this study were a mathematics teacher with 11 years of teaching experience at the junior high school level and six 9th-grade students who had an interest in mathematics from two different classes. The structure of collective argumentation shows that this learning focuses on students while the teacher acts as a facilitator. It can be seen from the more significant number of actions taken by students than teachers. In terms of participation, teachers more often act as ghostee, while students participate more as spokesman. Overall, this study reveals the structure of argumentation in solving geometry problems at each stage of Polya. Questions and explanations given by the teacher influence students' collective argumentation. A teacher must have questioning and communication skills so that students can actively participate in learning in the classroom.